57-----------------------
From -4 to 1 (range equals the y values)
Answer:
I am not sure but I think the correct answer is c
9514 1404 393
Answer:
a. 61
Step-by-step explanation:
The remainder theorem tells you the remainder of f(x)/(x -3) is equal to f(3). Using x=3 in the expression, we have ...
4x³ -2x² -10x +1
= ((4x -2)x -10)x +1
= ((4·3 -2)(3) -10)(3) +1 = (10·3 -10)(3) +1 = 20·3 +1
= 61
The remainder from division by (x -3) is 61.
X = cos(pi/6) = √3/2
y = sin(pi/6) = 1/2
So at point (√3/2, 1/2)